Prenatal Expression of MET Receptor Tyrosine Kinase in the Fetal Mouse Dorsal Raphe Nuclei and the Visceral Motor/Sensory Brainstem - Wu, Hsiao-Huei (2013)
Signaling via MET receptor tyrosine kinase (MET) has been implicated in a number of neurodevelopmental events, including cell migration, dendritic and axonal development and synaptogenesis. Related to its role in the development of forebrain circuitry, we recently identified a functional promoter variant of the MET gene that is associated with autism spectrum disorder (ASD). The association of the MET promoter variant rs1858830 C allele is significantly enriched in families with a child who has ASD and co-occurring gastrointestinal conditions. The expression of MET in forebrain had been mapped in detail in developing mouse and rhesus macaque. However, in mammal, its expression in the developing brainstem has not been studied extensively throughout developmental stages. Brainstem and autonomic circuitry are implicated in ASD pathophysiology and in gastrointestinal dysfunction. To advance our understanding of the neurodevelopmental influences of MET signaling in brainstem circuitry development, we employed in situ hybridization and immunohistochemistry to map the expression of Met and its ligand, Hgf, through prenatal development of the mouse midbrain and hindbrain. Our results reveal a highly selective expression pattern of Met in the brainstem: including a subpopulation of neurons in cranial motor nuclei (nVII, nA, and nXII), B6 subgroup of the dorsal raphe, Barrington’s nucleus, and a small subset of neurons in the nucleus of solitary tract. In contrast to Met, neither full length nor known splice variants of Hgf were localized in the prenatal brainstem. RT-PCR revealed Hgf expression in target tissues of Met-expressing brainstem neurons, suggesting that MET in these neurons may be activated by HGF from peripheral sources. Together, these data suggest that MET signaling may influence the development of neurons that are involved in central regulation of gastrointestinal function, tongue movement, swallowing, speech, stress, and mood.